The Application of Whole−Exome Sequencing in Patients With FUO - Guo, Wanru; Feng, Xuewen; Hu, Ming; Shangguan, Yanwan; Xia, Jiafeng; Hu, Wenjuan; Li, Xiaomeng; Zhang, Zunjing; Shi, Yunzhen; Xu, Kaijin (Frontiers in Cellular and Infection Microbiology, 2022)
Background Fever of unknown origin (FUO) is still a challenge for clinicians. Next-generation sequencing technologies, such as whole exome sequencing (WES), can be used to identify genetic defects in patients and assist in diagnosis. In this study, we investigated the application of WES in individuals with FUO. Methods We performed whole-exome sequencing on 15 FUO patients. Clinical information was extracted from the hospital information system. Results In 7/15 samples, we found positive results, including potentially causative mutations across eight different genes: CFTR, CD209, IRF2BP2, ADGRV 1, TYK2, MEFV, THBD and GATA2. Conclusions Our results show that whole-exome sequencing can promote the genetic diagnosis and treatment of patients with FUO.